The Moderating Effect of female director on the relationship between CSR and company performance: Evidence in from Indonesian Transportation Sector - asna, asna (Jurnal Riset Mahasiswa Akuntansi, 2024)
The current study investigates how female director moderates the relationship between CSR and company performance of transportation firms in Indonesia. Drawing on stakeholder theory and using data of Indonesian’s Transportation listed companies over the period 2019–2022, we examine the association between CSR, female director, and company performance. Particularly, we investigate whether CSR and female director contributes to improving company performance, and whether the relationship between CSR and company performance is moderated by female director. Our empirical findings suggest that firms with effective CSR exhibit company performance. The results also indicate that female director is positively associated with company performance. furthermore, the findings reveal that the positive relationship between CSR and company performance is negatively moderated by female director. Consequently, the study sheds light on female director, corporate social responsibility, and company performance from both a theoretical and empirical standpoint. The advantages of having female director and the possible impact of participating in CSR reporting should be known to regulators and stakeholders.